2017
DOI: 10.18203/2320-1770.ijrcog20172896
|View full text |Cite
|
Sign up to set email alerts
|

Causes and management of secondary postpartum haemorrhage in a tertiary medical college hospital in Bangladesh

Abstract: Background: Globally postpartum haemorrhage remains a leading cause of maternal death. It affects only 1-2% of postnatal women. This low incidence of secondary PPH and linkage to maternal morbidity rather than mortality was the reason for the little attention among obstetricians, but it is recently gaining importance and interest with the increase morbidity and mortality related to secondary PPH.Methods: A retrospective study was conducted on the diagnosed patients of secondary PPH admitted in Enam Medical Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This study identified 98 (49%) who needed an admission of more than 5 days, in agreement with a study by Kamrun Nessa et al conducted on 33 patients with a history of secondary PPH; 24 (73%) needed an admission of more than 5 days. This finding relates to surgical management and hysterectomies due to delays in seeking care rather than medical treatment, and this aggressive surgical intervention required longer hospitalizations [18]. We found a wide range of treatment modalities for the management of secondary PPH, ranging from medical to surgical, and about 33 (16.5%) patients responded to conservative management and 47 patients needed vaginal exploration after delivery.…”
Section: Discussionmentioning
confidence: 89%
“…This study identified 98 (49%) who needed an admission of more than 5 days, in agreement with a study by Kamrun Nessa et al conducted on 33 patients with a history of secondary PPH; 24 (73%) needed an admission of more than 5 days. This finding relates to surgical management and hysterectomies due to delays in seeking care rather than medical treatment, and this aggressive surgical intervention required longer hospitalizations [18]. We found a wide range of treatment modalities for the management of secondary PPH, ranging from medical to surgical, and about 33 (16.5%) patients responded to conservative management and 47 patients needed vaginal exploration after delivery.…”
Section: Discussionmentioning
confidence: 89%
“…In a study by Nessa et al caesarean section were common mode of delivery being 68.57% whereas delivered vaginally were only 37.14% cases. 12 Raji et al reported normal labour was seen in 31.51%, instrumental delivery 3.42%, spontaneous expulsion 2.74%, LSCS 61.65%, hysterotomy 0.68%. 13 Ghimire et al reported nearly 70% women underwent caesarean section.…”
Section: Discussionmentioning
confidence: 96%
“…They have used MVA for retained products of conception and retained clots. 14 The traditional causes of postpartum hemorrhage, which typically are retained placental fragments, are less likely to arise after C. section, because the delivery of the placenta is directly observed. 15,16 Eight patients (0.15%) who had delivered by caesarean section, developed secondary PPH, while six (0.26%) of patients who delivered vaginally developed secondary PPH.…”
Section: Discussionmentioning
confidence: 99%